Innovative Nerve Root Protection in Full-Endoscopic Facet-Resecting Lumbar Interbody Fusion: Controlled Cage Glider Rotation Using the GUARD (Glider Used As a Rotary Device) Technique - Yu-Chia Hsu; Hao-Chun Chuang; Wei-Lun Chang; Yuan-Fu Liu; Chao-Jui Chang; Yu-Meng Hsiao; Yi-Hung Huang; Keng-Chang Liu; Chien-Min Chen; Hyeun-Sung Kim; Cheng-Li Lin (Neurospine)
This video presents a case of L4–5 unstable spondylolisthesis treated with full-endoscopic transforaminal lumbar interbody fusion (Endo-TLIF), emphasizing the GUARD (Glider Used as a Rotary Device) technique for nerve root protection. This innovative approach involves controlled rotation of the cage glider before cage insertion to minimize the risk of nerve root injury, a significant complication in Endo-TLIF procedures. The GUARD technique, validated in previous cadaveric studies, provides enhanced safety during cage insertion by protecting the nerve root. A 48-year-old woman with a 3-year history of progressive low back pain and bilateral lower extremity radiculopathy (right-sided predominance) was diagnosed with L4–5 unstable spondylolisthesis and spinal stenosis. After failure of conservative management, she underwent uniportal full-endoscopic facet-resecting transforaminal lumbar interbody fusion using the GUARD technique. Postoperatively, the patient experienced significant symptomatic improvement and resolution of radiculopathy, without any intraoperative nerve root injury or postoperative neurological deficits. This case demonstrates the effectiveness of the GUARD technique in reducing neurological complications and improving patient outcomes.